Interprofessional primary care: indispensable for family physicians yet invisible to older patients. Issue 6 (2nd November 2022) - Sourial, Nadia; Hacker Teper, Matthew; Arsenault-Lapierre, Geneviève; Mehta, Kavita; Kay, Kelly; Vedel, Isabelle
ABSTRACT: There is growing consensus that interprofessional primary care is key to delivering timely, coordinated, and comprehensive care, especially in the older patient population who often live with complex and chronic needs. Despite significant investments in reforming health systems toward interprofessional primary care, there is a paucity of evidence describing the importance of interprofessional primary care for older patients and physicians. This qualitative descriptive study aimed to understand the use and utility of interprofessional primary care for older patients and family physicians from the perspective of different stakeholders within primary care in Ontario, Canada. Twenty-five semi-structured interviews (including 16 older patients, six family physicians, three primary care managers) and a focus group with 13 patient representatives were conducted. Our study found that while the benefits of interprofessional primary care teams for family physicians were clearly emphasized, stakeholders consistently reported that older patients often appeared to be unaware of the presence of, or roles played by, non-physician healthcare professionals in their clinic. Better transparency and education regarding available services and roles of different care providers may allow for more optimal use of interprofessional family medicine clinics by patients.